Decentralised systems - Definition and drivers in the current context - Sharma, A.; Tjandraatmadja, G.; Cook, Simon; Gardner, T. (I W A Publishing, 2013)
This paper explores the current context for decentralised approaches in the provision of urban water services. It examines the recent history of decentralised systems' implementation in Australia and identifies its drivers. The drivers included addressing capacity constraints of centralised systems, mitigating the environmental impact of urban development, and increasing the resilience of urban water systems to episodic droughts and the projected impacts of climate change. The concepts of integrated urban water management and water sensitive urban design were prevalent in many of the innovative approaches used for the provision of decentralised urban water services. However, there remains a degree of confusion among water professionals in the terminology adopted for on-site and decentralised systems. Based on a literature review, consultation with water industry professionals and examination of decentralised urban developments in Australia, this paper has developed a generalised definition of decentralised systems for adoption across the water sector. The definition encompasses the various development scales in which decentralised systems are implemented, and reflects the new functions and characteristics inherent to those systems. © CSIRO 2013.